Merkel cell carcinoma: a case report and literature review - Enrique, Soulé-Martínez Christian; Angel, Monroy-Ramírez Miguel; Michel, Jaimes-Durán Edwing; Leonel, Castellanos-Aguilar; Rafael, Ricarte-Almeida Eros; I., Lupián-Angulo Arianne (International Surgery Journal, 2021)
Merkel cell carcinoma (MCC) is a rare, but highly aggressive, malignant neuroendocrine tumor, with a higher prevalence in men, Caucasians, and the elderly. It is usually identified in photo-exposed areas such as the head, trunk, and extremities. It is related to locoregional recurrences and metastases, which conditions a high mortality rate. Currently, the pathogenesis is unclear, but it is related to ultraviolet radiation, immunosuppression, and polyomavirus infection. Prompt diagnosis and treatment are essential to improve the survival rate.